Economic evaluation of nurse led intermediate care versus standard care for post-acute medical patients: cost minimisation analysis of data from a randomised controlled trial. Issue 7493 (9th March 2005) - Walsh, Bronagh; Steiner, Andrea; Pickering, Ruth M; Ward-Basu, Jilly
Abstract: Objective To undertake an economic evaluation of nurse led intermediate care compared with standard hospital care for post-acute medical patients. Design Cost minimisation analysis from an NHS perspective, comprising secondary care, primary care, and community care, using data from a pragmatic randomised controlled trial. Setting Nurse led unit and acute general medical wards in large, urban, UK teaching hospital. Participants 238 patients. Outcome measure Costs to acute hospital trusts and to the NHS over six months. Results On an intention to treat basis, nurse led care was associated with higher costs during the initial admission period (nurse led care £7892 (14 970; €11 503), standard care £4810, difference £3082 (95% confidence interval £1161 to £5002)). During the readmission period, costs were similar (nurse led care £1444, standard care £1879, difference -£435, -£1406 to £536). Total costs at six months were significantly higher (nurse led care £10 529, standard care £7819, difference £2710, £518 to £4903). Sensitivity analyses suggested that the trend for nurse led care to be more expensive was maintained even with substantial cost reductions, although differences were no longer significant. Conclusion Acute hospitals may not be cost effective settings for nurse led intermediate care. Both inpatient and total costs were significantly higher for nurse led care than for standard care of post-acute medical patients, suggesting that this model of care should not be pursued unless clinical or organisational benefits justify the increased investment.